2023
DOI: 10.1002/fsn3.3828
|View full text |Cite
|
Sign up to set email alerts
|

Dietary acrylamide exposure and health risk assessment of pregnant women: A case study from Türkiye

Hilal Pekmezci,
Burhan Basaran

Abstract: This study aimed to determine the acrylamide exposure of pregnant women resulting from the consumption of bread, coffee, and French fries and to evaluate it in terms of carcinogenic and non‐carcinogenic health risks. Retrospective 24‐h food consumption data of pregnant women (n = 487) was obtained using the Food Frequency Questionnaire (FFQ). Dietary acrylamide exposure was calculated according to a deterministic model, and the data were assessed by hazard index (HI) and carcinogenic risk (CR). The mean daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…WHO estimated that for the general population, including children, the international mean dietary exposure to acrylamide in food is 1 μg/kg bw per day [ 78 ]. According to the same article, 4 μg/kg bw per day is considered to be the excessive dietary exposure to acrylamide [ 31 , [91] , [92] , [93] ]. Acrylamide is thought to be genotoxic, there is no safe threshold dose, and since the dangers posed by genotoxic substances are not species-specific, the relative cancer risk observed in animals is extrapolated to humans [ 31 ].…”
Section: Acrylamide and Health Risks In Human Beingsmentioning
confidence: 99%
See 1 more Smart Citation
“…WHO estimated that for the general population, including children, the international mean dietary exposure to acrylamide in food is 1 μg/kg bw per day [ 78 ]. According to the same article, 4 μg/kg bw per day is considered to be the excessive dietary exposure to acrylamide [ 31 , [91] , [92] , [93] ]. Acrylamide is thought to be genotoxic, there is no safe threshold dose, and since the dangers posed by genotoxic substances are not species-specific, the relative cancer risk observed in animals is extrapolated to humans [ 31 ].…”
Section: Acrylamide and Health Risks In Human Beingsmentioning
confidence: 99%
“…The amount of acrylamide in food should be follow the guideline ALARA (As Low As Reasonably Achievable) [ 36 ]. Bread, coffee, and French fries are examples of foods high in acrylamide that pregnant women should stay away from since they increase the risk of cancer in both the mother and the fetus [ 93 ]. Acrylamide is classified as a neo-formed toxin (NFT), meaning that it may have harmful effects on human health.…”
Section: Acrylamide and Health Risks In Human Beingsmentioning
confidence: 99%
“…Animals exposed to acrylamide may have decreased fertility, implantation abnormalities, and lower postnatal survival (ALKarim et al., 2015 ; Duan et al., 2015 ; Tyl & Friedman, 2003 ). Pekmezci and Basaran ( 2023 ) have shown that the exposure to acrylamide in pregnant women leads to an increased risk of cancer.…”
Section: Introductionmentioning
confidence: 99%